2021
DOI: 10.1136/bcr-2020-237032
|View full text |Cite
|
Sign up to set email alerts
|

Intra-abdominal small intestinal desmoid tumour mimicking GIST

Abstract: Desmoid tumours, also known as aggressive fibromatosis, are fibromuscular neoplasms that arise from mesenchymal cell lines. Desmoid tumours are usually benign and are locally aggressive tumours. We report a case of a 31-year-old man presenting with abdominal mass associated with dyspepsia and early satiety. CT scan demonstrated a large heterogeneous mass adherent to or arising from the jejunum. The patient underwent a successful elective exploratory laparotomy with resection of the tumour arising from the wall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Furthermore, desmoid tumors originating from the small bowel are exceedingly rare [7]. There are only a few such cases reported in the literature [17,18]. Many individuals with intra-abdominal desmoid tumorseither in the bowel or, more commonly, the mesenteryare asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, desmoid tumors originating from the small bowel are exceedingly rare [7]. There are only a few such cases reported in the literature [17,18]. Many individuals with intra-abdominal desmoid tumorseither in the bowel or, more commonly, the mesenteryare asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…Many individuals with intra-abdominal desmoid tumorseither in the bowel or, more commonly, the mesenteryare asymptomatic. However, particularly later in the disease course, patients can present with such signs and symptoms as palpable mass, nausea, early satiety, abdominal pain, and gastrointestinal bleeding [18]. Further complications include intestinal obstruction, bowel ischemia, ureteric obstruction, functional deterioration in ileoanal anastomosis (characteristically seen in patients who have undergone colectomy for FAP), abscess, and hepatic pneumatosis [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…GISTs are the most common mesenchymal tumors of the digestive system and occur most frequently in the stomach (50-60%), followed by the small intestine (30-35%) (1-2). It is generally believed that the prognosis of GISTs is poor, and there are currently few reports on GISTs (3)(4)(5)(6). In 2006, Miettinen et al (5) reported on the clinical, pathological, and molecular biological characteristics of 906 GIST cases, which represents a relatively large and comprehensive cohort of GIST studies.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally believed that the prognosis of small intestinal stromal tumors is poor, and there are currently few reports of these tumors (1)(2)(3)(4). In 2006, Miettinen et al (5) reported on the clinical, pathological, and molecular biological characteristics of 906 small intestinal stromal tumor cases; this study comprised a relatively large cohort, which facilitated the comprehensive investigation of small Case Report Fourth-line targeted drugs for the long-term treatment of patients with secondary gastrointestinal stromal tumors with multisite mutations: a case report intestinal stromal tumors.…”
Section: Introductionmentioning
confidence: 99%
“…The overall incidence rate of intra-abdominal AF is only 8%, [2] and occurrences in the small intestine are even rarer. While case reports have documented AF in the jejunum, ileum, and small intestine mesentery, [3][4][5] there are no reports of it occurring in the duodenum. Here, we report a rare case of small bowel obstruction caused by duodenum-derived AF with CTNNB1 T41A mutation.…”
Section: Introductionmentioning
confidence: 99%